Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
The formulation of Li1+x AaBbMmMn2-a-b-mO4-y active material addresses lithium loss in spinel oxides by promoting tetragonal spinel formation and stabilizing the structure, enhancing battery capacity and cycle life.
Patent Information
- Application Number
- CN202310729217.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-19
AI Technical Summary
Existing secondary batteries using spinel oxides face challenges in balancing capacity and cycle storage life due to excess Li entering the Mn position, leading to lithium loss and insufficient tetragonal spinel content.
A positive electrode active material comprising Li1+x AaBbMmMn2-a-b-mO4-y is formulated, where A includes elements like Ca, Sc, Ti, V, Cr, or Y, and B includes at least one of Ni, Al, Co or Fe, M includes at least one of W, Nb, Sb, P, La, Mo, Ta or Ce, controlling x, a, b, and m to promote tetragonal spinel formation and stabilize the structure with a suitable alkaline coating layer.
The active Li content is increased, and the material exhibits improved capacity and stability, resulting in enhanced battery performance with extended cycle life.
Smart Images

Figure CN119170793A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Secondary batteries are not only used in energy storage power systems such as hydropower, thermal, wind and solar power stations, but are also widely used in electric transportation vehicles such as electric bicycles, electric motorcycles, electric cars, as well as in military equipment, aerospace and other fields.
[0003] Spinel oxides are commonly used positive electrode active materials for secondary batteries. However, it is difficult to balance the capacity and cycle storage life of existing secondary batteries containing spinel oxides.
[0004] Public Content
[0005] In view of the technical problems existing in the background technology, the present application provides a positive electrode active material, aiming to solve the problems of low capacity and short cycle life of batteries containing the positive electrode active material.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, wherein the positive electrode active material comprises:
[0007] Li 1+x A a B b M m Mn 2-a-b-m O 4-y ,
[0008] Among them, A includes at least one of Ca, Sc, Ti, V, Cr, Sr, Y or Zr, B includes at least one of Ni, Al, Co or Fe, M includes at least one of W, Nb, Sb, P, La, Mo, Ta or Ce, 0.1<x≤1.1, 0.001≤a≤0.5, 0≤b≤1, 0≤m≤0.2, -0.5≤y≤1.
[0009] The present application at least includes the following beneficial effects: in the positive electrode active material of the present application, controlling the amount of x, i.e., the amount of excess Li in the positive electrode active material, is conducive to forming a sufficient amount of tetragonal spinel in the positive electrode active material, thereby increasing the capacity of the positive electrode active material; element A is an element that is easy to form an oxide containing a Li spinel structure, and the atomic radius of element A is large, so that the oxygen octahedral gap is reduced, thereby inhibiting Li from entering the Mn position. In addition, A will preferentially enter the Mn position, fill the Mn position, stabilize the octahedral gap, and thereby inhibit Li from entering the Mn position, so the doping element A and the above-mentioned a range In the range of x and a, the formation of spinel with excess Li can be promoted, which is beneficial for the phase state of part of the positive electrode active material to be tetragonal spinel, so that more Li is retained in the Li position, the active Li is increased to exert its capacity, and the capacity of the positive electrode active material is improved; in addition, within the range of the above x and a, the positive electrode active material also includes cubic spinel, and the cubic spinel has strong stability, so that the positive electrode active material has excellent stability. The positive electrode active material contains a sufficient amount of tetragonal spinel and part of cubic spinel, which improves the capacity of the battery containing it, and the battery has excellent cycle performance. The radius of element B is comparable to that of Mn, so it can be dispersed at the Mn site, and its low valence state can promote the valence state of Mn to rise, promoting Mn to become +4 valence, thereby inhibiting the Jan-Taylor effect of the positive electrode active material and improving the capacity of the positive electrode active material. Element M can form a strong bond with oxygen, stabilizing the positive electrode active material, especially the oxygen atoms on the surface of the grains, reducing surface side reactions, reducing side reactions between the positive electrode active material and the electrolyte, reducing oxygen loss in the positive electrode active material, reducing Mn dissolution, and improving the capacity of the positive electrode active material. At the same time, the positive electrode active material has excellent cycle performance.
[0010] In some embodiments of the present application, A includes at least one of Ca, Sc, Ti, V, Cr or Y. Thus, the capacity and stability of the positive electrode active material can be improved, the capacity of the battery containing the positive electrode active material can be improved, and the battery has excellent cycle performance.
[0011] In some embodiments of the present application, A includes at least one of Sc, V or Y. Thus, the capacity and stability of the positive electrode active material can be improved, the capacity of the battery containing the positive electrode active material can be improved, and the battery has excellent cycle performance.
[0012] In some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: 0.2≤x≤0.6, optionally 0.2≤x≤0.4; 0.01≤a≤0.4, optionally 0.05≤a≤0.3; 0.01≤b≤1, optionally 0.1≤b≤0.7; 0.001≤m≤0.2, optionally 0.01≤m≤0.1. Thus, the capacity and cycle life of the battery containing it are excellent.
[0013] In some embodiments of the present application, 1≤x / a≤10, and may be 2≤x / a≤7. Thus, within the above x / a range, the positive electrode active material can be promoted to exert a large capacity, and the capacity reduction caused by excessive A element can be reduced, thereby improving the capacity of the battery containing it, and the battery has excellent cycle performance.
[0014] In some embodiments of the present application, 0.001≤a+b+m≤1, and optionally, 0.3≤a+b+m≤0.7. Thus, within the range of a+b+m, the positive electrode active material maintains a spinel phase, and the capacity and cycle life of the battery containing the positive electrode active material are excellent.
[0015] In some embodiments of the present application, the positive electrode active material further includes a 1+x A a B b M m Mn 2-a-b-m O 4-y At least part of the surface of the alkaline coating layer. The alkaline coating layer can increase the pH value of the positive electrode active material, neutralize the acid generated by the oxidation of the electrolyte, thereby reducing the corrosion damage to the positive electrode active material, improving the stability of the positive electrode active material, and increasing the capacity of the battery containing it, while the battery has excellent cycle performance.
[0016] In some embodiments of the present application, the alkaline coating layer comprises D g+ d Z h+ z O 2- t Q - q , wherein D includes at least one of Li, Na, K, Be, Mg or Ca, Z includes at least one of B, Si, P or As, Q includes at least one of F, Cl, Br or I, g = 1 or 2, h = 3, 4 or 5, 1.5 ≤ (t + q) / z ≤ 5, 0 ≤ q / t ≤ 2. Therefore, the above-mentioned substance is a strong base weak acid salt, which is alkaline, but the alkalinity is not too strong, and has good compatibility with the positive electrode active material itself, excellent ion conductivity, can make the positive electrode active material play a large capacity, and the battery containing it has excellent capacity and cycle life.
[0017] In some embodiments of the present application, in the positive electrode active material, the mass proportion of the alkaline coating layer is 0.3%-5%, and optionally 1%-3%. Thus, when the mass proportion of the alkaline coating layer is within the above range, the capacity and cycle life of the battery containing it are excellent.
[0018] In some embodiments of the present application, the charging capacity of the positive electrode active material at 2.9V accounts for 10%-30% of the total charging capacity, and can be optionally 15%-25%. Thus, the proportion of the charging capacity at 2.9V to the total charging capacity is within the above range, so that the content of tetragonal spinel in the positive electrode active material is within a suitable range, and the excess Li at the Li position can just make up for the loss of active Li when the positive electrode active material is used in the battery, while making the structure of the positive electrode active material relatively stable, and the capacity and cycle life of the battery containing it are excellent.
[0019] In some embodiments of the present application, the pH value of the saturated aqueous solution of the positive electrode active material at 25° C. is 9-11.5, and can be optionally 10-11. Within the above pH value range, the acid generated by the oxidation of the electrolyte can be neutralized, thereby reducing the corrosion damage to the positive electrode active material, improving the stability of the positive electrode active material, and improving the capacity of the battery containing the positive electrode active material, while the battery has excellent cycle performance.
[0020] In some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions:
[0021] The volume average particle size D of the positive electrode active material v 50 is 1μm-30μm, optional is 2μm-10μm;
[0022] The BET specific surface area of the positive electrode active material is 0.1 m 2 / g-5m 2 / g, optional 0.2m 2 / g-2m 2 / g;
[0023] The tap density of the positive electrode active material is 1.5 g / cm 3 -3.0g / cm 3 , optional 2g / cm 3 -2.5g / cm 3 .
[0024] Therefore, when the volume average particle size D of the positive electrode active material v 50. When at least one of the BET specific surface area and the tap density is within the above range, the conduction distance of ions in the positive electrode active material is small and the surface side reactions are small, which promotes the positive electrode active material to exert its gram capacity and improves the capacity of the battery containing it. At the same time, the battery has excellent cycle performance.
[0025] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising:
[0026] LiA a B b M m Mn2-a-b-m O 4-y Mixing with a first lithium source and performing a first sintering to obtain a positive electrode active material, the positive electrode active material comprising:
[0027] Li 1+x A a B b M m Mn 2-a-b-m O 4-y ,
[0028] Among them, A includes at least one of Ca, Sc, Ti, V, Cr, Sr, Y or Zr, B includes at least one of Ni, Al, Co or Fe, M includes at least one of W, Nb, Sb, P, La, Mo, Ta or Ce, 0.1<x≤1.1, 0.001≤a≤0.5, 0≤b≤1, 0≤m≤0.2, -0.5≤y≤1.
[0029] Therefore, the positive electrode active material prepared in this application is a spinel structure LiA a B b M m Mn 2-a-b-m O 4-y and the first lithium source and perform the first sintering, in which LiA a B b M m Mn 2-a-b-m O 4-y Li is supplemented in the electrolyte so that excess Li enters the Li site, so that the obtained positive electrode active material contains a sufficient amount of tetragonal spinel and part of cubic spinel, has excellent capacity and stability, improves the capacity of the battery containing it, and the battery has excellent cycle performance.
[0030] In some embodiments of the present application, the first sintering temperature is 300° C.-600° C. At the above temperature, the positive electrode active material is promoted to include both tetragonal spinel and cubic spinel, thereby increasing the capacity of the battery containing the same, and the battery has excellent cycle performance.
[0031] In some embodiments of the present application, the LiA a B b M m Mn 2-a-b-m O 4-y The following steps are used to obtain the LiA a B b M m Mn 2-a-b-m O 4-y .
[0032] In some embodiments of the present application, the present invention further includes: mixing the positive electrode active material with an alkaline material, performing a third sintering, and a B b M m Mn 2-a-b-m O 4-y A basic coating is formed on at least a portion of the surface.
[0033] The third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application or the positive electrode active material prepared by the method described in the second aspect.
[0034] The fourth aspect of the present application provides a battery, which comprises the positive electrode sheet described in the third aspect of the present application. Thus, the battery has excellent capacity and cycle life.
[0035] A fifth aspect of the present application provides an electrical device, which includes the battery described in the fourth aspect.
[0036] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0038] Figure 1 is a schematic structural diagram of a battery according to one embodiment of the present application;
[0039] Figure 2 is a schematic structural diagram of a battery module according to an embodiment of the present application;
[0040] Figure 3 is a schematic structural diagram of a battery pack according to an embodiment of the present application;
[0041] Figure 4 yes Figure 3 Exploded diagram of
[0042] Figure 5 is a schematic diagram of an embodiment of an electrical device in which a battery is used as a power source;
[0043] Figure 6 is the XRD spectra of the positive electrode active materials of Example 1 and Comparative Example 1 of the present application;
[0044] Figure 7It is a first-cycle charging curve diagram of the button-type half-battery of Example 1 and Comparative Example 1 of the present application.
[0045] Description of reference numerals:
[0046] 1: Secondary battery; 2: Battery module; 3: Battery pack; 4: Upper case; 5: Lower case. DETAILED DESCRIPTION
[0047] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0048] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0049] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0050] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0052] With the technological development and increasing demand for electric vehicles and rechargeable mobile devices, secondary batteries, as a representative of the new energy field, have also seen rapid development in related research. Lithium-ion batteries have a small size and weight, making them easy to carry and use; they have a high specific energy and can provide a larger amount of energy storage. In addition, lithium-ion batteries have no memory effect and do not need to be fully discharged and recharged, so they have broad application prospects.
[0053] Spinel-structured oxides have high voltage, good overcharge resistance, easy preparation and low cost, so they have become one of the popular positive electrode active materials for lithium-ion batteries.
[0054] However, existing spinel oxides have the following problems: on the one hand, the excess Li in the spinel oxide easily enters the Mn position, resulting in the inactivity of the excess Li, and the Li in the adjacent Li position also loses activity, resulting in lithium loss; on the other hand, the existing spinel oxides are mostly cubic spinels, and even if there are tetragonal spinels, the content of tetragonal spinels is insufficient, resulting in the easy loss of active lithium in the positive electrode active material. The loss of active lithium leads to a decrease in the capacity of the spinel oxide.
[0055] In the present application, the amount of x, i.e., the amount of excess Li in the positive electrode active material, is controlled to supplement active lithium, promote the formation of a sufficient amount of tetragonal spinel, and improve the capacity of the positive electrode active material; the positive electrode active material is doped with element A and its doping amount is controlled. The atomic radius of element A is large, which reduces the oxygen octahedral gap and inhibits Li from entering the Mn position; in addition, A will preferentially enter the Mn position (oxygen octahedral gap), fill the Mn position, stabilize the octahedral gap, and then inhibit Li from entering the Mn position. Therefore, doping element A within the above range of a can promote The formation of spinel with excess Li is beneficial to the phase state of part of the positive electrode active material being tetragonal spinel, so that more Li is retained in the Li position, the active Li is increased to exert its capacity, and the capacity of the positive electrode active material is improved; in addition, within the range of the above x and a, the positive electrode active material also includes cubic spinel, so that the positive electrode active material has excellent stability, the positive electrode active material contains a sufficient amount of tetragonal spinel and part of cubic spinel, the capacity of the battery containing it is improved, and the battery has excellent cycle performance.
[0056] The positive electrode active material disclosed in the embodiment of the present application is suitable for secondary batteries, and the battery disclosed in the embodiment of the present application can be used in electrical equipment using the battery as a power source or various energy storage systems using the battery as an energy storage element. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.
[0057] In a first aspect, the present application provides a positive electrode active material, the positive electrode active material comprising:
[0058] Li 1+x A a B b M m Mn 2-a-b-m O 4-y ,
[0059] Among them, A includes at least one of Ca, Sc, Ti, V, Cr, Sr, Y or Zr, B includes at least one of Ni, Al, Co or Fe, M includes at least one of W, Nb, Sb, P, La, Mo, Ta or Ce, 0.1<x≤1.1, 0.001≤a≤0.5, 0≤b≤1, 0≤m≤0.2, -0.5≤y≤1.
[0060] The present application at least includes the following beneficial effects: in the positive electrode active material of the present application, firstly, the amount of x, i.e., the amount of excess Li in the positive electrode active material, is controlled to supplement active lithium, promote the formation of a sufficient amount of tetragonal spinel in the positive electrode active material, and improve the capacity of the positive electrode active material; secondly, for the excess Li, doping element A and controlling its doping amount can promote the positive electrode active material to form more Li-excess spinel LMO, which is beneficial for the phase state of part of the positive electrode active material to be tetragonal spinel, so that the excess Li is as much as possible. stays at the Li position, increasing the active Li in the positive electrode active material and improving the capacity of the positive electrode active material; finally, since tetragonal spinel is unstable and has poor reversibility, within the range of the above x and a, the positive electrode active material also includes part of cubic spinel. Cubic spinel has strong stability. By controlling x and a, the positive electrode active material contains sufficient tetragonal spinel and part of cubic spinel at the same time. The combined effect of x and a improves the capacity of the battery containing it, and the battery has excellent cycle performance.
[0061] The unit cell of the tetragonal system has the shape of a square column, and the unit cell parameters are a=b≠c, α=β=γ=90°; while the cubic system has four cube diagonal direction triple axis characteristic symmetry elements, and its unit cell parameters are a=b=c, α=β=γ=90°. In the embodiment of the present application, Li 1+x A a B b M m Mn 2-a-b-m O 4-y A sufficient amount of tetragonal spinel can provide a large amount of active lithium, while cubic spinel has good stability. The two complement each other, so that the positive electrode active material has a high active lithium content and strong stability, thereby improving the capacity of the positive electrode active material and at the same time, the positive electrode active material has excellent cycle performance.
[0062] It should be noted that the phase characterization method of the positive electrode active material in the present application can be characterized by XRD. Specifically, the peak at the 33° position in the XRD spectrum represents tetragonal spinel.
[0063] It is understandable that in the embodiment of the present application, when the battery is charged, part of the lithium in the tetragonal spinel in the positive electrode active material will be preferentially released and transformed into cubic spinel, so when the positive electrode potential is charged to >3.0V, the positive electrode contains no or very little tetragonal spinel. When the battery is discharged again to a positive electrode potential of 2.5V, the tetragonal spinel will be restored again.
[0064] In some embodiments of the present application, A includes at least one of Ca, Sc, Ti, V, Cr or Y. The above doping elements will preferentially enter the Mn site, fill the Mn site, stabilize the octahedral gap, and then inhibit Li from entering the Mn site, so that the positive electrode active material contains a sufficient amount of tetragonal spinel, increase active Li, and improve the capacity of the positive electrode active material. In other embodiments of the present application, A includes at least one of Sc, V or Y.
[0065] In some embodiments of the present application, the charging capacity of the positive electrode active material at 2.9V accounts for 10%-30% of the total charging capacity. For example, the charging capacity of the positive electrode active material at 2.9V accounts for 10%-30% of the total charging capacity. For example, the charging capacity of the positive electrode active material at 2.9V can be 10%-30%, 11%-29%, 12%-28%, 13%-27%, 14%-26%, 15%-25%, 16%-24%, 17%-23%, 18%-22%, 19%-21%, etc.
[0066] Specifically, the ratio of the charging capacity of the positive electrode active material at 2.9V to the total charging capacity is proportional to the content of tetragonal spinel in the positive electrode active material. At this 2.9V potential, the active Li of the positive electrode active material comes from tetragonal spinel, that is, the greater the ratio of the charging capacity of the positive electrode active material at 2.9V to the total charging capacity, the higher the content of tetragonal spinel in the positive electrode active material, and the more active lithium can be provided. When the ratio of the charging capacity of the positive electrode active material at 2.9V to the total charging capacity is within this range, the excess Li at the Li position in the positive electrode active material is sufficient to make up for the loss of active Li when it is used in the battery. At the same time, the positive electrode active material contains an appropriate amount of cubic spinel, which has a stable structure, improves the capacity of the positive electrode active material, and has excellent cycle performance, thereby improving the capacity of the battery containing it, and the battery has excellent cycle performance. In other embodiments of the present application, the above-mentioned positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y In the embodiment, the charging capacity of the positive electrode active material at 2.9V accounts for 15%-25% of the total charging capacity.
[0067] It can be understood that the “total charge capacity” refers to the total capacity of a battery containing the positive electrode active material of the embodiment of the present application from the start of charging to the end of charging, that is, the charge capacity of the battery from 0V to 4.35V.
[0068] It is understood that the "ratio of the charging capacity of the positive electrode active material at 2.9V to the total charging capacity" in the present application has a well-known meaning in the art and can be measured using instruments and methods well-known in the art. For example, it can be obtained by the following method:
[0069] In a battery using the positive electrode active material of the embodiment of the present application as the positive electrode and Li as the negative electrode, the battery is charged to 4.35V at a constant current rate of 0.1C, and the proportion of the charging capacity of 2.8-3.1V to the total charging capacity is calculated.
[0070] In some embodiments of the present application, the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-yIn the above, x can be 0.1<x≤1.1, for example, 0.15≤x≤1.05, 0.18≤x≤1, 0.2≤x≤0.9, 0.3≤x≤0.8, 0.4≤x≤0.7, 0.5≤x≤0.6, etc. Thus, x represents the excess Li in the positive electrode active material. As x increases, the active Li in the positive electrode active material increases, and the capacity of the positive electrode active material increases. When x is within the above range, the structural instability of the positive electrode active material caused by excessive Li content can be reduced, and excessive Li entering the Mn position can be reduced. In addition, excess Li also promotes the formation of tetragonal spinel, so that there is a sufficient amount of tetragonal spinel and part of cubic spinel in the positive electrode active material, which improves the capacity of the positive electrode active material and has excellent cycle performance. In other embodiments of the present application, 0.2≤x≤0.6, for example, 0.2≤x≤0.4.
[0071] It should be noted that the ratio of each element in the positive electrode active material in the present application refers to the ratio of each element in the positive electrode active material before the positive electrode active material is made into a positive electrode sheet and assembled into a battery for formation. Those skilled in the art can understand that in the positive electrode sheet, battery or electrical device, due to the formation and circulation processes, some elements will be consumed. Even if the measured ratio of the corresponding elements of the positive electrode active material is not within the above range, it should fall within the scope of the present application. For example, batteries appearing on the market usually cycle and age after assembling the battery, and thus, the lithium content in the positive electrode active material is less than 1+x. At the same time, if the positive electrode sheet and the negative electrode sheet use a lithium supplement, after the battery undergoes formation and circulation processes, the measured lithium content in the positive electrode active material will be greater than 1+x.
[0072] In some embodiments of the present application, the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y , a can be 0.001≤a≤0.5, for example, 0.001≤a≤0.5, 0.005≤a≤0.5, 0.1≤a≤0.5, 0.15≤a≤0.45, 0.2≤a≤0.4, 0.25≤a≤0.35, 0.25≤a≤0.3, etc. Specifically, the positive electrode active material includes the A element at this content, which can promote the formation of spinel with excess Li, which is beneficial for the phase state of part of the positive electrode active material to be tetragonal spinel, so that more Li is retained in the Li position, increasing the capacity of the active Li to exert its capacity, and improving the capacity of the positive electrode active material. In some other embodiments of the present application, the above-mentioned positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O4-y Here, a can be 0.01≤a≤0.4, for example, 0.05≤a≤0.3.
[0073] In some embodiments of the present application, the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y In the formula, b can be 0≤b≤1, for example, 0≤b≤0.9, 0.1≤b≤0.9, 0.2≤b≤0.8, 0.3≤b≤0.7, 0.4≤b≤0.6, etc. Specifically, the B element is equivalent to the radius of Mn and can be dispersed in the Mn position. Its low valence state can promote the valence state of Mn to rise, and promote Mn to become +4 valence, thereby inhibiting the Jahn-Taylor effect of the positive electrode active material and improving the capacity of the positive electrode active material. The doping amount b of the B element is within the above range, so that the positive electrode active material has a spinel structure, and can slow down the structural decay of the positive electrode active material and the dissolution of the Mn element, thereby improving the capacity of the positive electrode active material. At the same time, its cycle performance is excellent, thereby improving the capacity of the battery containing it, and the battery has excellent cycle performance. In other embodiments of the present application, the above-mentioned positive electrode active material Li 1+ x A a B b M m Mn 2-a-b-m O 4-y In the equation, b can be 0.01≤b≤1, for example, 0.1≤b≤0.7.
[0074] In some embodiments of the present application, the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y In the formula, m can be 0≤m≤0.2, for example, 0.001≤m≤0.2, 0.01≤m≤0.15, 0.05≤m≤0.12, 0.06≤m≤0.1, 0.07≤m≤0.09, etc. Therefore, this content of element M can form a strong bond with oxygen, stabilize the positive electrode active material, especially the oxygen atoms on the surface of the grains, reduce surface side reactions, reduce the side reactions between the positive electrode active material and the electrolyte, reduce the loss of oxygen in the positive electrode active material, reduce the dissolution of Mn, and increase the capacity of the positive electrode active material. At the same time, its cycle performance is excellent, thereby increasing the capacity of the battery containing it, and the battery has excellent cycle performance. In some other embodiments of the present application, the above-mentioned positive electrode active material Li 1+ x A a B b M m Mn2-a-b-m O 4-y In the equation, m can be 0.001≤m≤0.2, for example, 0.01≤m≤0.1.
[0075] It can be understood that in the embodiments of the present application, the lower limit of b and m is 0, which means that there may be no b and m in the positive electrode active material.
[0076] In some embodiments of the present application, the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y In the equation, y can be -0.5≤y≤1, for example, -0.5≤y≤0.9, -0.4≤y≤0.8, -0.3≤y≤0.7, -0.2≤y≤0.6, -0.1≤y≤0.5, 0≤y≤0.4, 0.1≤y≤0.3, etc.
[0077] It should be noted that in the positive electrode sheet, battery or electrical device, due to the battery cycle and other processes, the positive electrode active material may release oxygen from the lattice, and the oxygen element in the positive electrode active material may be lost, so the measured oxygen element content 4-y in the positive electrode active material may be less than 4. In addition, there are many oxygen-rich situations in the positive electrode active material, such as the dissolution of Mn, the entry of Li into the Mn position, and another example is that a part of Li4Mn5O in the positive electrode active material 12 phase, therefore, the measured oxygen element content 4-y in the positive electrode active material may be greater than 4.
[0078] In some embodiments of the present application, the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y In the formula, x / a can be 1≤x / a≤10, for example, 1≤x / a≤9, 2≤x / a≤8, 3≤x / a≤7, 4≤x / a≤6, etc. Specifically, the larger the x, the higher the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y The more excess Li there is, the easier it is for Li to enter the Mn position, and the more doping elements A are needed to inhibit Li from entering the Mn position and promote Li to stay in the Li position. Within the above x / a range, the capacity of the positive electrode active material is increased, and its cycle performance is excellent, thereby increasing the capacity of the battery containing it, and the battery has excellent cycle performance. In other embodiments of the present application, the above positive electrode active material Li1+x A a B b M m Mn 2-a-b-m O 4-y In this case, x / a can be 2≤x / a≤7.
[0079] In some embodiments of the present application, the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y The contents of A, B and M satisfy the following relationship: 0.001≤a+b+m≤1, for example, 0.001≤a+b+m≤0.9, 0.01≤a+b+m≤0.9, 0.1≤a+b+m≤0.9, 0.2≤a+b+m≤0.8, 0.3≤a+b+m≤0.7, 0.4≤a+b+m≤0.6, etc. Thus, a+b+m represents the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y The amount of doping elements in the positive electrode active material can significantly inhibit the Jiang-Taylor effect of the positive electrode active material, making the positive electrode active material a spinel structure, and improving the positive electrode active material Li 1+x A a B b M m Mn 2-a-b-m O 4-y The structural stability of the positive electrode active material Li is improved, thereby increasing the capacity of the battery containing it, and the battery has excellent cycle performance. 1+x A a B b M m Mn 2-a-b-m O 4-y In the equation, we can take 0.3≤a+b+m≤0.7.
[0080] In some embodiments of the present application, the positive electrode active material further includes a 1+x A a B b M m Mn 2-a-b-m O 4-y At least part of the surface of the alkaline coating. During the battery charge and discharge cycle, the electrolyte is easily oxidized to produce acid (such as HF). The alkaline coating can reduce the replacement of active Li by the acidified electrolyte, especially reducing Li 1+x Aa B b M m Mn 2-a-b-m O 4-y The excess Li in the cathode is replaced, thereby reducing the loss of active Li; the alkaline coating layer can also neutralize part of the acid, reduce the corrosion and damage of the acid on the surface of the cathode active material, increase the capacity of the cathode active material, and at the same time its cycle performance is excellent, thereby increasing the capacity of the battery containing it, and the battery has excellent cycle performance.
[0081] It is understood that the alkaline coating layer refers to the coating on the Li 1+x A a B b M m Mn 2-a-b-m O 4-y The alkaline substance on the outer surface of the particle may have a pH value of 7.5-13, for example, the pH value of the alkaline coating layer may be 7.5-12.5, 8-12, 8.5-11.5, 9-11, 9.5-10.5, etc. For example, the alkaline coating layer may include a strong base and a weak acid salt.
[0082] It is understood that the positive electrode active material also includes a Li 1+x A a B b M m Mn 2-a-b-m O 4-y At least part of the alkaline coating on the surface includes Li 1+x A a B b M m Mn 2-a-b-m O 4-y The surface of the 1+ x A a B b M m Mn 2-a-b-m O 4-y The entire surface of the substrate is covered with an alkaline coating layer.
[0083] In some embodiments of the present application, Li 1+x A a B b M m Mn 2-a-b-m O 4-y The entire surface of the positive electrode is covered with an alkaline coating layer, which plays a role in isolating the electrolyte, reducing the loss of active lithium, reducing the corrosion and damage to the surface of the positive electrode active material, and improving the capacity and cycle performance of the positive electrode active material, thereby improving the capacity of the battery containing it, and the battery has excellent cycle performance.
[0084] In some embodiments of the present application, the alkaline coating layer comprises D g+ d Z h+ z O 2- t Q - q , specifically, D g+ d Z h+ z O 2- t Q - q It is a strong base weak acid salt, wherein D includes at least one of Li, Na, K, Be, Mg or Ca, Z includes at least one of B, Si, P or As, Q includes at least one of F, Cl, Br or I, g = 1 or 2, h = 3, 4 or 5, 1.5≤(t+q) / z≤5, 0≤q / t≤2. For example, 1.5≤(t+q) / z≤4.5, 2≤(t+q) / z≤4, 2.5≤(t+q) / z≤3.5, etc., (t+q) / z represents the number of anions that the core element Z needs to match, 0.1≤q / t≤1.9, 0.5≤q / t≤1.5, 1≤q / t≤1.5, etc., q / t represents the amount of elements substituted at the O position, specifically, the above alkaline coating layer can increase the pH value of the material, the above D g+ d Z h+ z O 2- t Q - q It is alkaline, but not too alkaline; in addition, D g+ d Z h+ z O 2- t Q - q It has good compatibility with positive electrode active materials and excellent ion conductivity, which increases the capacity of positive electrode active materials. At the same time, it has excellent cycle performance, thereby increasing the capacity of the battery containing it, and the battery has excellent cycle performance.
[0085] In some embodiments of the present application, D g+ d Z h+ z O 2- t Q - qIt can include small molecule weak acid and strong base salts, such as lithium phosphate, sodium phosphate, lithium borate, sodium borate, lithium silicate, sodium silicate, etc. It can also include polymers, such as lithium polyphosphate (Li n+2 P n O 3n+1 ).
[0086] In some embodiments, in the positive electrode active material, the mass proportion of the alkaline coating layer is 0.3%-5%. For example, the mass proportion of the alkaline coating layer can be 0.3%-4.5%, 0.5%-4%, 1%-3.5%, 1.5%-3%, 2%-2.5%, etc. Specifically, in the positive electrode active material, the mass proportion of the alkaline coating layer is within the above range, which can play a good protective role on the positive electrode active material, while reducing the hindrance of the excessive coating amount to the transmission of lithium ions, thereby increasing the capacity of the positive electrode active material, and its cycle performance is excellent, thereby increasing the capacity of the battery containing it, and the battery has excellent cycle performance. In other embodiments of the present application, in the positive electrode active material, the mass proportion of the alkaline coating layer is 1%-3%.
[0087] In some embodiments of the present application, the pH value of the saturated aqueous solution of the positive electrode active material at 25°C is 9-11.5. For example, the pH value of the saturated aqueous solution of the positive electrode active material at 25°C can be 9-11.2, 9.2-11, 9.5-10.8, 9.8-10.5, 9.9-10, etc. When the pH value of the saturated aqueous solution of the positive electrode active material at 25°C is within the above range, it can neutralize part of the acid produced by the oxidation of the electrolyte, reduce the corrosion and damage of the acid on the surface of the positive electrode active material, and reduce the deterioration of the processing performance of the positive electrode active material caused by excessive alkalinity, thereby improving the capacity of the positive electrode active material, and the battery has excellent cycle performance. In other embodiments of the present application, the pH value of the saturated aqueous solution of the positive electrode active material is 10-11.
[0088] Specifically, the "pH value of the saturated aqueous solution of the positive electrode active material at 25° C." in the present application has a well-known meaning in the art and can be measured using instruments and methods well-known in the art. For example, it can be obtained by the following method:
[0089] The positive electrode active material and pure water were mixed in a mass ratio of 1:9, magnetically stirred for 30 minutes, and then placed in a constant temperature water bath at 25°C for 1.5 hours. The pH value of the mixture was tested according to GB / T 9724-2007.
[0090] In some embodiments of the present application, the volume average particle size D of the positive electrode active material is v 50 is 1 μm-30 μm, for example, the volume average particle size D of the positive electrode active materialv 50 can be 1 μm-29 μm, 3 μm-25 μm, 5 μm-23 μm, 10 μm-20 μm, 13 μm-15 μm, etc. In other embodiments of the present application, the volume average particle size D of the positive electrode active material is v 50 is 2μm-10μm.
[0091] In this application, the volume average particle size D v 50 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%, for example, with reference to the standard GB / T 19077-2016, and measured using a laser particle size analyzer (such as Malvern Master Size 3000).
[0092] In some embodiments of the present application, the BET specific surface area of the positive electrode active material is 0.1 m 2 / g-5m 2 / g, for example, the BET specific surface area of the positive electrode active material can be 0.1 m 2 / g-4.5m 2 / g,0.5m 2 / g-4m 2 / g,1m 2 / g-3.5m 2 / g, 1.5m 2 / g-3m 2 / g,2m 2 / g-2.5m 2 In some other embodiments of the present application, the BET specific surface area of the positive electrode active material is 0.2 m 2 / g-2m 2 / g.
[0093] In this application, the "BET specific surface area of the positive electrode active material" of this application has a well-known meaning in the art and can be measured by instruments and methods well-known in the art. For example, it can be obtained by the following method: using the American Micromeritics multi-station fully automatic BET specific surface area and pore analyzer GeminiVII2390, taking about 7g of sample and putting it into a 9cc long tube with a bulb, degassing at 200℃ for 2h, and then putting it into the host to test to obtain the BET (specific surface area) data of the positive electrode active material.
[0094] In some embodiments of the present application, the tap density of the positive electrode active material is 1.5 g / cm 3 -3.0g / cm 3 For example, the tap density of the positive electrode active material can be 1.5 g / cm 3 -2.8g / cm 3 , 1.8g / cm 3-2.5g / cm 3 , 2.0g / cm 3 -2.3g / cm 3 In some other embodiments of the present application, the tap density of the positive electrode active material is 2 g / cm 3 -2.5g / cm 3 .
[0095] In this application, tap density refers to the mass per unit volume of the powder in the container after being tapped under specified conditions. The tap density of the positive electrode active material can be determined by the following method:
[0096] Load the weighed positive electrode active material into the measuring cylinder of the vibration device, and fix the measuring cylinder on the support. Turn the cam, and the directional rod drives the support to slide up and down and hit the anvil. Vibrate 250±15 times per minute for 12 minutes. Measure the volume of the positive electrode active material in the measuring cylinder. The ratio of the mass of the positive electrode active material to the volume is the tap density of the positive electrode active material.
[0097] The calculation formula of tap density is: ρbt=m0 / V
[0098] Where, ρbt is the tap density, g / cm 3
[0099] m0——mass of positive electrode active material, g
[0100] V——Volume of positive electrode active material after compaction (volume of measuring cup), cm 3 .
[0101] Specifically, when the volume average particle size D of the positive electrode active material of the present application is v 50. When at least one of the BET specific surface area and the tap density is within the above range, the conduction distance in the positive electrode active material is small and the surface side reactions are small, which promotes the positive electrode active material to exert its gram capacity and improves the capacity of the battery containing it. At the same time, the battery has excellent cycle performance.
[0102] The second aspect of the present application provides a method for preparing the positive electrode active material according to the first aspect, comprising:
[0103] S100: LiA a B b M m Mn 2-a-b-m O 4-y Mixing with a first lithium source and performing a first sintering to obtain a positive electrode active material, the positive electrode active material comprising:
[0104] Li 1+x A a B b Mm Mn 2-a-b-m O 4-y ,
[0105] Wherein, A includes at least one of Ca, Sc, Ti, V, Cr, Sr, Y or Zr, B includes at least one of Ni, Al, Co or Fe, M includes at least one of W, Nb, Sb, P, La, Mo, Ta or Ce, 0.1<x≤1.1, 0.001≤a≤0.5, 0≤b≤1, 0≤m≤0.2, -0.5≤y≤1
[0106] With LiA a B b M m Mn 2-a-b-m O 4-y Mixed with the first lithium source and sintered, the spinel structure of LiA a B b M m Mn 2-a-b-m Supplementing Li on the basis of O4 makes it easy for excess Li to enter the Li site, which is beneficial to the formation of sufficient tetragonal spinel in the positive electrode active material and improves the capacity of the positive electrode active material.
[0107] In some embodiments of the present application, the above-mentioned LiA a B b M m Mn 2-a-b-m O 4-y and the first lithium source are placed in a muffle furnace in an air atmosphere for a first sintering, and then cooled to room temperature, and mechanically crushed to obtain a positive electrode active material, wherein the temperature of the first sintering is 300°C-600°C. For example, the temperature of the first sintering can be 300°C-590°C, 320°C-550°C, 350°C-500°C, 380°C-480°C, 350°C-450°C, 380°C-400°C, etc. Controlling the first sintering temperature within the above range is conducive to the formation of a sufficient amount of tetragonal spinel in the positive electrode active material, and is conducive to obtaining a positive electrode active material containing a sufficient amount of tetragonal spinel and a portion of cubic spinel, thereby improving the capacity and stability of the positive electrode active material, thereby improving the capacity of the battery containing it, and the battery has excellent cycle performance.
[0108] In some embodiments of the present application, the first sintering time is 5h-50h, for example, the first sintering time can be 5h-45h, 10h-40h, 15h-35h, 20h-30h, etc.
[0109] In some embodiments of the present application, the LiA a B b M m Mn2-a-b-m O 4-y The following steps are used to obtain:
[0110] S1000: Mix the second lithium source, A source, B source, M source and Mn source, and perform a second sintering to obtain LiA a B b M m Mn 2-a-b-m O 4-y
[0111] In some embodiments of the present application, the second lithium source, A source, B source, M source and Mn source are mixed and placed in a muffle furnace in an air atmosphere for a second sintering, and then cooled to room temperature and mechanically crushed to obtain LiA a B b M m Mn 2-a-b- m O 4-y , wherein the second sintering temperature is 700-1100°C, for example, the second sintering temperature can be 700°C-1000°C, 750°C-950°C, 800°C-900°C, etc., and the second sintering time is 5h-50h, for example, the second sintering time can be 5h-45h, 10h-40h, 15h-35h, 20h-30h, etc. Under the above second sintering conditions, spinel structured LiA a B b M m Mn 2-a-b-m O 4-y .
[0112] It should be noted that the Li source, A source, B source, M source and Mn source in the present application are conventional materials in the art, and those skilled in the art can select them according to actual conditions. For example, the Li source may include at least one of Li2CO3, LiHCO3, LiOH, Li2O2, Li2O, Li2NO3, Li2C2O4, Li3PO4, Li2SO4, and Li3BO3; the A source may include at least one of the carbonate, hydroxide, oxide, nitrate, oxalate, phosphate, sulfate, and borate of A; the B source may include at least one of the carbonate, hydroxide, oxide, nitrate, oxalate, phosphate, sulfate, and borate of A; Including at least one of the carbonates, hydroxides, oxides, nitrates, oxalates, phosphates, sulfates and borates of B; the M source may include at least one of the carbonates, hydroxides, oxides, nitrates, oxalates, phosphates, sulfates and borates of M; the Mn source may include at least one of the carbonates, hydroxides, oxides, nitrates, oxalates, phosphates, sulfates and borates of M.
[0113] It should be noted that if the positive electrode active material does not include the B element and / or the M element, then in the process of preparing the positive electrode active material, accordingly, no B source and / or M source is added.
[0114] In some embodiments of the present application, the method for preparing the positive electrode active material further comprises:
[0115] S200: Mixing the positive electrode active material with an alkaline material and performing a third sintering process. a B b M m Mn 2-a-b- m O 4-y At least part of the surface forms an alkaline coating
[0116] The alkaline material and Li 1+x A a B b M m Mn 2-a-b-m O 4-y Mixing to achieve coating and protection. The third sintering can enhance the alkaline coating layer and Li 1+x A a B b M m Mn 2-a-b-m O 4-y The binding force promotes the comprehensiveness of the coating and improves the protective effect of the alkaline coating layer.
[0117] In some embodiments of the present application, the temperature of the third sintering is 200°C-700°C, for example, the third sintering temperature can be 200°C-650°C, 250°C-600°C, 300°C-550°C, 350°C-500°C, 400°C-450°C, etc. Within the third sintering temperature range, the alkaline coating layer and Li 1+x A a B b M m Mn 2-a-b-m O 4-y The binding force promotes comprehensive coating and improves the protective effect of the alkaline coating layer.
[0118] In some embodiments of the present application, the third sintering time is 1 h-10 h. For example, the third sintering time may be 1 h-9 h, 2 h-8 h, 3 h-7 h, 4 h-6 h, etc.
[0119] The third aspect of the present application provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present application or the positive electrode active material prepared by the method described in the second aspect.
[0120] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0121] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.
[0122] The positive electrode active material includes the positive electrode active material described in the first aspect of the present application or the positive electrode active material prepared by the method described in the second aspect.
[0123] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bind the positive electrode active material and the binder to the positive electrode current collector. The present application does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0124] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA) and polyvinyl alcohol (PVA).
[0125] These materials are all commercially available.
[0126] The fourth aspect of the present application provides a battery, which comprises the positive electrode sheet described in the third aspect of the present application. Thus, the battery has excellent capacity and cycle life.
[0127] A battery is a battery that can be used again by recharging the active materials after discharge.
[0128] It can be understood that the battery proposed in this application is a lithium-ion battery.
[0129] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0130] [Negative electrode]
[0131] In a battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0132] The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.
[0133] The specific type of the negative electrode active material is not limited, and active materials known in the art that can be used for the negative electrode of the battery can be used, and those skilled in the art can choose according to actual needs. As an example, the negative electrode active material may include, but is not limited to, one or more of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-based materials and tin-based materials. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds (such as silicon monoxide), silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. These materials can all be obtained commercially.
[0134] In some embodiments, in order to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.
[0135] The negative electrode active material layer may also optionally include a binder, a conductive agent and other optional auxiliary agents.
[0136] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0137] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0138] As examples, other optional additives may include thickening and dispersing agents (eg, sodium carboxymethylcellulose CMC-Na), and PTC thermistor materials.
[0139] [Electrolyte]
[0140] The electrolyte may include an electrolyte salt and a solvent.
[0141] As an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0142] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0143] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0144] [Isolation film]
[0145] As the above-mentioned isolation membrane, the present application has no special restrictions and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can include a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0146] The embodiment of the present application has no particular limitation on the shape of the battery, which can be cylindrical, square or any other shape. Figure 1 A square-structured battery 1 is shown as an example.
[0147] In some embodiments, the battery may include an outer packaging for packaging the positive electrode sheet, the negative electrode sheet, and the electrolyte.
[0148] In some embodiments, the outer package may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.
[0149] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly. The electrode assembly is packaged in the receiving cavity. The number of electrode assemblies contained in the battery can include one or more, which can be adjusted according to demand.
[0150] In some embodiments, the outer packaging of the battery may include a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.
[0151] The outer packaging of the battery may also include a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0152] In some embodiments, the batteries may be assembled into a battery module. The battery module may contain multiple batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0153] Figure 2 2 is an example of a battery module 2. Figure 2 In the battery module 2, the multiple batteries 1 may be arranged in sequence along the length direction of the battery module 2. Of course, they may also be arranged in any other manner. Further, the multiple batteries 1 may be fixed by fasteners.
[0154] The battery module 2 may also include a housing having a storage space, in which a plurality of batteries 1 are stored. In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0155] Figure 3 and 4 The battery pack 3 is used as an example. Figure 3 and 4 The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0156] The fifth aspect of the present application provides an electrical device, which includes the battery described in the fourth aspect. Specifically, the battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.
[0157] Figure 5 The electrical equipment is used as an example, and the electrical equipment includes a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.
[0158] As another example, the electric device may include a mobile phone, a tablet computer, and a notebook computer. The electric device is usually required to be thin and light, and a battery may be used as a power source.
[0159] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0160] Example 1
[0161]
Li 1.4 Sc 0.1 Mn 1.9 O4 preparation
[0162] Li2O3, Sc2O3 and Mn3O4 (the molar ratio of Li, Sc and Mn is 1:0.1:1.9) are mixed evenly, and then the temperature is increased to 850℃ (the second sintering temperature) at a heating rate of 5℃ / min in a muffle furnace. After sintering for 10h, the temperature is naturally cooled to room temperature to obtain LiSc 0.1 Mn 1.9 O4.
[0163] LiSc 0.1 Mn 1.9 O4 and Li (molar ratio 1:0.4) were mixed and sintered at 450°C (first sintering temperature) for 15 hours and then naturally cooled to room temperature to obtain the positive electrode active material Li 1.4 Sc 0.1 Mn 1.9 O4.
[0164]
Preparation of positive electrode
[0165] The Li 1.4 Sc 0.1 Mn 1.9 O4, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are dispersed in a proper amount of solvent N-methylpyrrolidone (NMP) in a weight ratio of 90:5:5, and stirred and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode aluminum foil collector, and after drying, cold pressing, and slitting, the positive electrode sheet is obtained.
[0166]
Preparation of negative electrode sheet
[0167] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0168]
Preparation of electrolyte
[0169] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7 to obtain a mixed solvent, and then LiPF6 was dissolved in the mixed solvent and stirred to obtain an electrolyte.
[0170]
Isolation film
[0171] Glass fiber is used as the isolation membrane.
[0172] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried secondary battery. After vacuum packaging, standing, formation, and shaping processes, a secondary battery is obtained.
[0173] The secondary batteries containing the positive electrode active materials of Examples 2-26 are the same as those of Example 1 except for the different parameters (see Table 1).
[0174] Embodiment 27
[0175] [Li with alkaline coating on the surface 1.4 Sc 0.1 Mn 1.9 O4 preparation】
[0176] Li2O3, Sc2O3 and Mn3O4 (the molar ratio of Li, Sc and Mn is 1:0.1:1.9) are mixed evenly, and then the temperature is increased to 850℃ (the second sintering temperature) at a heating rate of 5℃ / min in a muffle furnace. After sintering for 10h, the temperature is naturally cooled to room temperature to obtain LiSc 0.1 Mn 1.9 O4.
[0177] LiSc 0.1 Mn 1.9 O4 and Li (molar ratio 1:0.4) were mixed and sintered at 450℃ (first sintering temperature) for 15h and then cooled naturally to room temperature to obtain Li 1.4 Sc 0.1 Mn 1.9 O4.
[0178] The alkaline material and Li 1.4 Sc 0.1 Mn 1.9 O4 is mixed evenly according to the coating mass ratio, and then the temperature is raised to 500°C and kept for 5 hours to obtain the positive electrode active material.
[0179]
Preparation of positive electrode
[0180] The positive electrode active material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) prepared above are dispersed in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5, and stirred and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode aluminum foil collector, and after drying, cold pressing, and slitting, a positive electrode sheet is obtained.
[0181]
Preparation of negative electrode sheet
[0182] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0183]
Preparation of electrolyte
[0184] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7 to obtain a mixed solvent, and then LiPF6 was dissolved in the mixed solvent and stirred to obtain an electrolyte.
[0185]
Isolation film
[0186] Glass fiber is used as the isolation membrane.
[0187] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried secondary battery. After vacuum packaging, standing, formation, and shaping processes, a secondary battery is obtained.
[0188] The secondary batteries containing positive electrode active materials of Examples 28-32 are the same as those of Example 27 except for different parameters (see Table 1).
[0189] The secondary battery containing the positive electrode active material of Example 33 is the same as that of Example 1 except for different parameters (see Table 1).
[0190] Comparative Example 1
[0191]
Li 1.4 Mn2O4 preparation
[0192] Li2O3 and Mn2O3 (the molar ratio of Li to Mn is 1.4:2) are mixed in the agate ball mill of a planetary ball mill, and the raw materials are ground at a speed of 600r / min. Then, the temperature is increased to 850℃ (the second sintering temperature) in a muffle furnace at a heating rate of 5℃ / min. After sintering for 10h, the temperature is naturally cooled to room temperature to obtain the positive electrode active material Li 1.4 Mn2O4.
[0193]
Preparation of positive electrode
[0194] The Li 1.4 Mn2O4, conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and N-methylpyrrolidone (NMP) are stirred and mixed evenly in a weight ratio of 60:5:5:30 to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode aluminum foil collector, and the positive electrode sheet is obtained after drying, cold pressing, and slitting.
[0195]
Preparation of negative electrode sheet
[0196] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0197]
Preparation of electrolyte
[0198] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7 to obtain a mixed solvent, and then LiPF6 was dissolved in the mixed solvent and stirred to obtain an electrolyte.
[0199]
Isolation film
[0200] Glass fiber is used as the isolation membrane.
[0201] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried secondary battery. After vacuum packaging, standing, formation, and shaping processes, a secondary battery is obtained.
[0202] Comparative Example 2
[0203]
Li 1.4 Sc 0.6 Mn 1.4 O4 preparation
[0204] Li2O3, Sc2O3 and Mn2O3 (the molar ratio of Li, Sc and Mn is 1:0.6:1.4) are mixed evenly, and then the temperature is increased to 850℃ (the second sintering temperature) at a heating rate of 5℃ / min in a muffle furnace. After sintering for 10 hours, the temperature is naturally cooled to room temperature to obtain black LiSc 0.6 Mn 1.4 O4.
[0205] LiSc 0.1 Mn 1.9 O4 and Li (molar ratio 1:0.4) were mixed and sintered at 450°C (first sintering temperature) for 15 hours and then naturally cooled to room temperature to obtain the positive electrode active material Li 1.4 Sc 0.6 Mn 1.4 O4.
[0206]
Preparation of positive electrode
[0207] The Li 1.4 Sc 0.6 Mn 1.4 O4, conductive agent carbon black and binder polyvinylidene fluoride (PVDF) are dispersed in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a weight ratio of 90:5:5, and stirred and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode aluminum foil collector, and after drying, cold pressing and slitting, the positive electrode sheet is obtained.
[0208]
Preparation of negative electrode sheet
[0209] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0210]
Preparation of electrolyte
[0211] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), organic solvents ethylene carbonate (EC) / ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3 / 7 to obtain a mixed solvent, and then LiPF6 was dissolved in the mixed solvent and stirred to obtain an electrolyte.
[0212]
Isolation film
[0213] Glass fiber is used as the isolation membrane.
[0214] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried secondary battery, and the secondary battery is obtained after vacuum packaging, standing, forming, and shaping. The composition of the positive electrode active material in the battery of Examples 1-33 of the present application and Comparative Examples 1-2 is shown in Table 1.
[0215] Table 1
[0216]
[0217]
[0218] In Table 1, “ / ” means no addition.
[0219] Performance Test:
[0220] 1. XRD diagram of positive electrode active material. XRD diagrams of the positive electrode active materials of Example 1 and Comparative Example 1 are obtained. Figure 6 .
[0221] 2. Test on the proportion of the 2.9V charging capacity of the positive electrode active material to the total charging capacity:
[0222] Taking Example 1 as an example, in a battery using the positive electrode active material of Example 1 as the positive electrode and Li as the negative electrode, the battery is charged to 4.35V at a current constant current of 0.1C. The charging curves of Example 1 and Comparative Example 1 are as follows: Figure 7As shown, the proportion of the charging capacity of 2.8-3.1V to the total charging capacity is calculated, and the results are shown in Table 1.
[0223] The testing process of the proportion of the charging capacity of the positive electrode active material 2.9 to the total charging capacity of Example 2-33 and Comparative Example 1-2 is the same as above.
[0224] 3. Battery capacity and cycle life test:
[0225] Taking Example 1 as an example, the secondary battery of Example 1 is charged to 4.25V at a rate of 0.33C, and then discharged to 3.0V at 0.33C. The first discharge capacity divided by the mass of the positive electrode active material is the first cycle capacity (referred to as capacity). After that, it is charged to 4.25V at 1C and then charged to 0.05C at a constant voltage, and then discharged to 3.0V at 1C, and then the repeated charge and discharge of 1C_0.05C_1C is repeated. The number of repeated charge and discharge is the number of cycles. When the discharge capacity decays to 80% of the initial capacity or the total number of cycles calculated by the positive electrode active mass decays to 80mAh / g (whichever condition is reached first) is the cycle life. The results are shown in Table 2.
[0226] Depend on Figure 6 It can be seen that the positive electrode active material of Example 1 of the present application has a peak at 33° ( Figure 6 It can be seen that tetragonal spinel is contained therein, while there is no peak at the 33° position in comparative example 1, which does not contain tetragonal spinel.
[0227] Depend on Figure 7 It can be seen that the 2.9V charging capacity content of Example 1 of the present application accounts for a non-zero proportion of the total charging capacity, indicating that the positive electrode active material contains tetragonal spinel, while the 2.9V charging capacity content in Comparative Example 1 accounts for a zero proportion of the total charging capacity, indicating that there is no tetragonal spinel in the positive electrode active material of Comparative Example 1.
[0228] The test process of the battery capacity and cycle life of Examples 2-33 and Comparative Examples 1-2 is the same as above, and the results are shown in Table 2.
[0229] Table 2
[0230]
[0231]
[0232] It can be seen from Table 2 that in Examples 1 to 33 of the present application, the initial capacity of the secondary batteries is all above 100 mA·h / g, and the capacity and cycle life are excellent. It can be seen that within the above ranges of x and a, the positive electrode active material contains a sufficient amount of tetragonal spinel and a portion of cubic spinel, which improves the capacity of the positive electrode active material, and at the same time its cycle performance is excellent, which improves the capacity of the battery containing it, and at the same time the battery has excellent cycle performance.
[0233] There is no element A in comparative example 1, and the amount a value of element A in comparative example 2 is not in the range of 0.001-0.5, and its cycle performance and storage performance are significantly lower than those of the embodiments of the present application.
[0234] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises: Li 1+x A a B b M m Mr 2-a-b-m O 4-y , Among them, A includes at least one of Ca, Sc, Ti, V, Cr, Sr, Y or Zr, B includes at least one of Ni, Al, Co or Fe, M includes at least one of W, Nb, Sb, P, La, Mo, Ta or Ce, 0.1<x≤1.1, 0.001≤a≤0.5, 0≤b≤1, 0≤m≤0.2, -0.5≤y≤1.
2. The positive electrode active material according to claim 1, characterized in that A includes at least one of Ca, Sc, Ti, V, Cr or Y.
3. The positive electrode active material according to claim 1 or 2, characterized in that: A includes at least one of Sc, V or Y.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The positive electrode active material satisfies at least one of the following conditions: 0.2≤x≤0.6, which can be 0.2≤x≤0.4; 0.01≤a≤0.4, optional 0.05≤a≤0.3; 0.01≤b≤1, optional 0.1≤b≤0.7; 0.001≤m≤0.2, optionally 0.01≤m≤0.
1.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that 1≤x / a≤10, optionally 2≤x / a≤7.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that 0.001≤a+b+m≤1, which can be optionally 0.3≤a+b+m≤0.
7.
7. The positive electrode active material according to any one of claims 1 to 6, characterized in that The positive electrode active material also includes a Li 1+x A a B b M m Mn 2-a-b-m O 4-y A basic coating on at least part of the surface.
8. The positive electrode active material according to claim 7, characterized in that The basic coating layer comprises D g+ d Z h+ z O 2- t Q - q , wherein D includes at least one of Li, Na, K, Be, Mg or Ca, Z includes at least one of B, Si, P or As, Q includes at least one of F, Cl, Br or I, g=1 or 2, h=3, 4 or 5, 1.5≤(t+q) / z≤5, 0≤q / t≤2.
9. The positive electrode active material according to claim 7 or 8, characterized in that: In the positive electrode active material, the mass proportion of the alkaline coating layer is 0.3%-5%, and can be optionally 1%-3%.
10. The positive electrode active material according to any one of claims 1 to 9, characterized in that The charging capacity of the positive electrode active material at 2.9V accounts for 10%-30% of the total charging capacity, and can be optionally 15%-25%.
11. The positive electrode active material according to any one of claims 1 to 10, characterized in that The pH value of the saturated aqueous solution of the positive electrode active material at 25° C. is 9-11.5, and can be optionally 10-11.
12. The positive electrode active material according to any one of claims 1 to 11, characterized in that The positive electrode active material satisfies at least one of the following conditions: The volume average particle size D of the positive electrode active material v 50 is 1μm-30μm, optional is 2μm-10μm; The BET specific surface area of the positive electrode active material is 0.1 m 2 / g-5m 2 / g, optional 0.2m 2 / g-2m 2 / g; The tap density of the positive electrode active material is 1.5 g / cm 3 -3.0g / cm 3 , optional 2g / cm 3 -2.5g / cm 3 .
13. A method for preparing a positive electrode active material, characterized in that: include: LiA a B b M m Mn 2-a-b-m O 4-y Mixing with a first lithium source and performing a first sintering to obtain a positive electrode active material, the positive electrode active material comprising: Li 1+x A a B b M m Mr 2-a-b-m O 4-y , Among them, A includes at least one of Ca, Sc, Ti, V, Cr, Sr, Y or Zr, B includes at least one of Ni, Al, Co or Fe, M includes at least one of W, Nb, Sb, P, La, Mo, Ta or Ce, 0.1<x≤1.1, 0.001≤a≤0.5, 0≤b≤1, 0≤m≤0.2, -0.5≤y≤1.
14. The method according to claim 13, characterized in that The LiA a B b M m Mn 2-a-b-m O 4-y The following steps are used to obtain the LiA a B b M m Mn 2-a-b-m O 4-y .
15. The method according to claim 13 or 14, characterized in that The first sintering temperature is 300°C-600°C.
16. The method according to any one of claims 13 to 15, characterized in that Also includes: The positive electrode active material is mixed with an alkaline material and subjected to a third sintering. a B b M m Mn 2-a-b-m O 4-y A basic coating is formed on at least a portion of the surface.
17. A positive electrode plate, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 12 or the positive electrode active material prepared by the method according to any one of claims 13 to 16.
18. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 17.
19. An electrical equipment, characterized in that: Comprising the battery of claim 18.
Citation Information
Patent Citations
Method for preparing doping lithium-enriching spinelle lithium manganese oxide
CN101117234A
Power spinel lithium manganese oxide anode material and preparation method thereof
CN101807682A
Cathode material of lithium ion battery and preparation method of cathode material
CN102683669A
Cathode materials, cathodes, and lithium secondary batteries containing spinel-structured lithium manganese-based cathode active materials
CN110582875A
Positive electrode material, positive electrode plate, battery and electric equipment
CN116230918A
